Synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an important intermediate for (3S,4R)-Cisapride - Shirode, Nilesh M.; Likhite, Anjali P.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2008)
An efficient synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an useful intermediate for the chiral synthesis of important drug molecule Cisapride and its analogs, from enantiopure 4-formylazetidin-2-one is described. Synthesis of trans as well as cis isomers of 4-amino-3-methoxypiperidine from 4-formylazetidin-2-one is also achieved in good yield. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: 4-aminopiperidine; azetidin-2-ones; Cisapride; Staudinger reaction; stereoselective synthesis